2231. Long-Term Immunogenicity of Four Doses and Four Double Doses vs. Standard Doses of Hepatitis B Vaccination in HIV-Infected Adults: An Extension of a Randomized Controlled Trial. (26th November 2018) - Chaiwarith, Romanee; Praparattanapan, Jutarat; Wipasa, Jiraprapa; Chaiklang, Kanokporn; Supparatpinyo, Khuanchai
Abstract: Background: Previous studies showed that the response rate to standard hepatitis B (HepB) vaccination schedule among HIV-infected patients ranged between 33.3 and 65% due to an impaired response. However, we have reported that the response rate was not different from four doses and four double doses schedule. This study followed those patients for at least 3 years aimed to evaluate the efficacy of the three regimens. Methods: From February 4, 2011 to May 4, 2012, 132 HIV-infected adults who had CD4+ cell counts >200 cells/mm 3, undetectable plasma HIV-1 RNA, and were negative for all hepatitis B virus markers were 1:1:1 randomly assigned to receive one of three recombinant vaccine (Hepavax-Gene ® Berna, Korea) regimens: 20 μg IM at months 0, 1, and 6 (standard doses group, n = 44), 20 μg IM at Months 0, 1, 2, 6 (four doses group, n = 44), or 40 μg IM at Months 0, 1, 2, and 6 (four double doses group, n = 44). Between January 2015 and January 2016, 126 participants were evaluated; 42 in the "standard doses group", 43 in the "four doses group", and 41 in the "four double doses group." Results: At a median duration of 49.6 months (range 40.6, 53.7) after vaccine regimen completion, the percentages of responders with anti-HBs ≥10 mIU/mL were 57.1% (95% CI, 41.5–72.8%) in the Standard doses group; 76.7% (95% CI 63.6–89.9%) in the Four doses group ( P = 0.067); and 80.5% (95% CI 67.8–93.2%) in the Four double doses group ( P = 0.033 vs. the standard group). Factor associated with a responder was vaccination schedule (either four standard doses or four double doses) and younger age. Conclusion: Despite highly effective of standard HBV vaccination schedule at 6 months after completion of vaccine regimen, long-term immunogenicity was lower than the four double doses regimen among HIV-infected adults with CD4+ cell counts >200 cells/mm 3 and undetectable plasma HIV-1 RNA. Disclosures: All authors: No reported disclosures.